PERANCANGAN PROTOTYPE APLIKASI MOBILE SMARTPHONE KEPANDUAN UNTUK ANGGOTA PRAMUKA - Zenmira, Kharisma Nanda; Abdila, Abu Bakar (Program Studi Pendidikan Seni Rupa FBS UNJ, 2025)
The advancement of digital technology has transformed youth learning patterns, particularly among Generation Z and Alpha who prefer visual and interactive media. However, scout education in Indonesia still mainly applies conventional methods. This study aims to design a prototype of a mobile scouting application as an alternative learning medium for scout members. Using the Research and Development (R&D) method with a 4P level 4 approach, the prototype includes features such as scouting materials, interactive quizzes, digital compass, maps, and e-books, all designed with visual communication principles. The prototype received positive feedback from target users.